Similarities and perspectives on the two C's—Cancer and COVID‐19. (31st March 2021) - Thachil, Jecko; Khorana, Alok; Carrier, Marc
Abstract: COVID‐19 continues to dominate the health‐care burden in the twenty‐first century. While health‐care professionals around the world try their best to minimize the mortality from this pandemic, we also continue to battle the high mortality from different types of cancer. For the hemostasis and thrombosis specialist, these two conditions present some unusual similarities including the high rate of thrombosis and marked elevation of D‐dimers. In this forum article, we discuss these similarities and provide some considerations for future research and therapeutic trials.